Exploring factors that impact uptake of risk-reducing bilateral salpingo-oophorectomy (RRBSO) in high-risk women. Issue 1 (January 2020) - Hickey, Martha; Rio, Ines; Trainer, Alison; Marino, Jennifer L.; Wrede, C. David; Peate, Michelle
Abstract: Objective: Only risk-reducing bilateral salpingo-oophorectomy (RRBSO) has been shown to reduce ovarian cancer deaths in high-risk women. Uptake of RRBSO is, however, suboptimal and reasons are not well defined. More information is needed about the barriers to RRBSO and patient needs for information and care. Methods: Cross-sectional study including the Perception of Cancer Risk Scale, factors affecting decision-making about RRBSO, and unmet information needs were measured using a purpose-designed questionnaire. Results: Of the 193 high-risk women aged 30 to 50 approached, 60 (31%) agreed to participate. Respondents were either considering or had recently undergone premenopausal RRBSO. Most (49/60) had no personal history of cancer; 11/60 had previous breast cancer. Overall, responses did not differ between pre- and post-RRBSO participants. The main barriers to RRBSO were surgical menopause and loss of fertility. Other concerns included the impact on sexual function and bone health. Reduction in ovarian cancer risk and prolonged life expectancy were the main drivers for RRBSO. Participants understood that RRBSO reduced cancer risk, although most substantially overestimated their personal ovarian cancer risk. High-risk women wanted more information about how to manage the short- and long-term consequences of surgical menopause. Conclusions: Concerns about surgical menopause and loss of fertility are barriers to RRBSO for high-risk women despite understanding the benefits of reduced cancer risk. There is an unmet need for more information about effectively managing the noncancer consequences of RRBSO in premenopausal women. N/A: Video Summary: http://links.lww.com/MENO/A478 . Abstract : Supplemental Digital Content is available in the text